UAV - Digital Terrain Elevation Model (DTM) from Stordalen Mire UAV Mire - Abisko Scientific Research Station (Swedish Polar Research Secretariat, 2025)
Digital Surface Model generated from photos taken from an UAV platform using photo-stereography techniques. Nominal pixel size is 5 cm.
Abisko Scientific Research Station (2025). UAV - Digital Terrain Elevation Model (DTM) from Stordalen Mire UAV Mire, 2024-06-12 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/SfH9IQ_3z9UDb_Rfflv3VaXU
Keywords: SITES Spectral; Calibration/Validation; Digital Elevation / Digital Surface Models; Ecosystem functions; NDVI; Plant Phenology; Reflectance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap